Pet odtenkov trajnosti med slovenskimi porabniki - Kos Koklič, Mateja (Akademija MM, 2019)
This paper presents a segmentation model of sustainably oriented consumers in Slovenia, where sustainability is understood as a holistic concept with an environmental, social, and economic component. Hence, our study also differs substantially from similar studies in the literature, which are mainly limited to the environmental category. For the segmentation we use psychographic variables, which are defined in the literature as those that have the highest potential impact on the sustainable consumer behavior. The analysis is based on a sample of 462 Slovenian respondents; the sample is representative of sex and age according to the Slovenian consumer population. Segmentation grouping by K-means classification and multivariate analysis show five statistically distinct segments named: the responsibles, the aware, the economically oriented, the declarants, and the uninterested. Among them, the largest segments are the responsibles and the declarants. Our segmentation model also provides useful implications for the practice of sustainable marketing.
Keywords: consumers; marketing; potrošniki; Slovenia; Slovenija; sustainable development; trajnostni razvoj; trženje